The use of a new 2D array of diodes for small-field dosimetry of a CyberKnife equipped with a novel multi-leaf collimator. (October 2020) - Biasi, G; Munoz, L; Hug, B; Ebert, M A; Petasecca, M; Bucci, J; Jackson, M; Rosenfeld, A B
Abstract: In the present work, we reported on the use of a new 2D array of diodes, the Duo, for dosimetry of small beams produced with a CyberKnife system, and shaped with a novel multi-leaf collimator, the InCise 2.